Peripheral Ulcerative Keratitis Associated with Autoimmune Disease: Pathogenesis and Treatment - Yan Cao; Wensong Zhang; Jie Wu; Hong Zhang; Hongyan Zhou (Journal of Ophthalmology)
Peripheral ulcerative keratitis (PUK) is type of crescent-shaped inflammatory damage that occurs in the limbal region of the cornea. PUK is always combined with an epithelial defect and the destruction of the peripheral corneal stroma. PUK may have a connection to systemic conditions, such as long-standing rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Wegener granulomatosis (WG), relapsing polychondritis, classic polyarteritis nodosa and its variants, microscopic polyangiitis, and Churg-Strauss syndrome. However, the most common connection is with RA, which is also the focus of this review. The pathogenesis of PUK is still unclear. It is thought that circulating immune complexes and cytokines exert an important influence on the progression of this syndrome. Treatment is applied to inhibit certain aspects of PUK pathogenesis.